2017
DOI: 10.3233/wor-172603
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Model of Occupational Self Efficacy in improving the cognitive functioning of individuals with brain injury: A pre- and post-intervention study

Abstract: Abstract.BACKGROUND: Individuals diagnosed with a Traumatic Brain Injury (TBI) often experience major limitations in returning to work despite participating in rehabilitation programmes. Objective: The aim of the study was to determine whether individuals who sustained a traumatic brain injury experienced improved cognitive functioning after participating in an intervention programme that utilizes the Model of Occupational Self-Efficacy (MOOSE). PARTICIPANTS: Ten (10) individuals who were diagnosed with a mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Function and participation were measured differently in all eight studies. One of the two studies in the field-of-work practice demonstrated an improvement in cognition [ 55 ]. In that study, seven of 10 participants returned to work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Function and participation were measured differently in all eight studies. One of the two studies in the field-of-work practice demonstrated an improvement in cognition [ 55 ]. In that study, seven of 10 participants returned to work.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining participants in the nine studies using physical rehabilitation included people with stroke [47][48][49][50][51], diabetic foot ulcerations [52], traumatic brain injury [53], and upper and lower limb injuries [49]. In the field of work practice, one study included nursing auxiliaries working in a residential facility for people with intellectual disabilities [54] while another study included participants with traumatic brain injuries [55].…”
Section: Reporting Of Participantmentioning
confidence: 99%
“…Developed in South Africa, the MOOSE is a client-centred, evidence-based model demonstrating an 80% success in RTW for individuals with disabilities 21 . The MOOSE has a client-centred dynamic staged approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only three papers came from LMICs and described computerised cognitive rehabilitation, cognitive music therapy and occupational therapy [86][87][88].…”
Section: Multi-componentmentioning
confidence: 99%